STUDI TENTANG KEMAMPUAN GURU MENERAPKAN METODE PROBLEM SOLVING DALAM PROSES BELAJAR MENGAJAR MATA PELAJARAN PPKN - Sri Utami (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
Based on research show that teachers are gradually learning activities in class. The class action research has largely been to apply the ethods of problem solving. It can be seen from the observations using the observation sheet,in each cyle of their research efforts of teachers to correct the deficiencies that occur mainly in the first cycle and the second cycle.The ability of teacher to apply problem solving method in teaching is requirement that must be met in an effort to create teaching and leraningproblem in accordance with the teaching plan and train students to think critically.The best way for learning to master,understand and have the skills to apply methods of problem solving in the learning process. The key must be mastered before teaching skills, questioning skills, present tip of, holding a variation, explain the opening and closing lessons, guided,small group discussions, manage the classroom, small group, individual and surveillance of learning resources.